Mathematical Model of Effect of Number of Pulses of Pulsed Laser on Formation Process of Plasma - Mousa, S. K. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The effect of number of pulses of pulsed laser on materials is studied analytically, different pulses has been used with the same delay time. The depth of possible damage to the surface of copper and titanium as well as depth of the crater to both materials were considered in this study. The study revealed that linear model is only possible when estimating depth of possible damage for copper material, this means that the depth of possible damage increases with the increment of number of laser pulses .As for titanium material, it is found the relationship is nonlinear. The depth of possible damage of titanium and copper is not the same, and copper seems to be more predictable than titanium.